Cloud, Fog, or Edge: Where to Compute? - Kimovski, Dragi; Matha, Roland; Hammer, Josef; Mehran, Narges; Hellwagner, Hermann; Prodan, Radu (IEEE internet computing, 2021)
The computing continuum extends the high-performance cloud data centers with energy-efficient and low-latency devices close to the data sources located at the edge of the network. However, the heterogeneity of the computing continuum raises multiple challenges related to application management. These include where to offload an application—from the cloud to the edge—to meet its computation and communication requirements. To support these decisions, we provide, in this article, a detailed performance and carbon footprint analysis of a selection of use case applications with complementary resource requirements across the computing continuum over a real-life evaluation testbed.